Grocery Stores Empowerment through Sampoerna Retail Community (SRC) Program in Ponorogo Regency from Maqashid Sharia Perspective - Febya Nur Hanifah; Mohammad Ridwan (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: The rapid growth of modern retail in Indonesia, such as Indomaret and Alfamart, has created major challenges for the sustainability of traditional grocery stores. This condition demands empowerment so that grocery stores are able to survive and adapt in the midst of increasingly competitive retail competition. One form of intervention in empowering grocery stores is the Sampoerna Retail Community (SRC) program, an initiative of PT HM Sampoerna Tbk. This program aims to improve the welfare of business actors, which in an Islamic perspective can be studied through the maqashid sharia approach. This study aims to analyze how the implementation of the SRC program impacts the performance of grocery stores in Ponorogo Regency from maqashid sharia perspective. Research Methods: The research method used is field research with a qualitative approach. Data were collected through interviews, observations, and documentation. To ensure the data validity, triangulation sources and techniques was used. The informants in this study include eight SRC store owners and a SRC coach. Results: The research findings show that SRC program, which focuses on three main aspects (store management, digitalization, and improved accessibility), is able to bring positive changes to grocery stores in economic, social and psychological aspects. However, the implementation has not been fully optimized, especially in digitalization aspect, which is influenced by the culture of shopkeepers and the activeness of the program assistants. Conclusion: The SRC program contributes positively to the welfare of the fostered store owners, which is marked by improved store performance and is in line with maqashid sharia. Although the program does not directly integrate sharia principles, it still reflects sharia values, such as justice, helping, and social welfare.